mHealth adoption in low-resource environments : a review of the use of mobile healthcare in developing countries - Chib, Arul (2014)
The acknowledged potential of using mobile phones for improving healthcare in low-resource environments of developing countries has yet to translate into significant mHealth policy investment. The low uptake of mHealth in policy agendas may stem from a lack of evidence of the scalable, sustainable impact on health indicators. The mHealth literature in low- and middle-income countries reveals a burgeoning body of knowledge; yet existing reviews suggest that the projects yields mixed results. This paper adopts a stage-based approach to understand the varied contributions to mHealth research. The heuristic of input-mechanism-outputs is proposed as a tool to categorize mHealth studies. This review (63 papers comprising 53 studies) reveals that mHealth studies in developing countries tend to concentrate on specific stages, principally on pilot projects that adopt a deterministic approach to technological inputs [n=2], namely introduction and implementation. Somewhat less studied research designs that demonstrate evidence of outputs [n=15], such as improvements in healthcare processes and public health indicators. The review finds a lack of emphasis on studies that provide theoretical understanding of adoption and appropriation of technological introduction that produces measurable health outcomes. As a result, there is a lack of dominant theory, or measures of outputs relevant to making policy decisions. Future work needs to aim for establishing theoretical and measurement standards, particularly from social scientific perspectives, in collaboration with researchers from the domains of information technology and public health. Priorities should be set for investments and guidance in evaluation disseminated by the scientific community to practitioners and policymakers.